Reassessing granzyme B: unveiling perforin-independent versatility in immune responses and therapeutic potentials - Thompson, Raylynn; Cao, Xuefang (Frontiers in Immunology, 2024)
The pivotal role of Granzyme B (GzmB) in immune responses, initially tied to cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells, has extended across diverse cell types and disease models. A number of studies have challenged conventional notions, revealing GzmB activity beyond apoptosis, impacting autoimmune diseases, inflammatory disorders, cancer, and neurotoxicity. Notably, the diverse functions of GzmB unfold through Perforin-dependent and Perforin-independent mechanisms, offering clinical implications and therapeutic insights. This review underscores the multifaceted roles of GzmB, spanning immunological and pathological contexts, which call for further investigations to pave the way for innovative targeted therapies.